2004
DOI: 10.1037/0022-0167.51.1.103
|View full text |Cite
|
Sign up to set email alerts
|

The Asian American Racism-Related Stress Inventory: Development, Factor Analysis, Reliability, and Validity.

Abstract: The development of the 29-item Asian American Racism-Related Stress Inventory (AARRSI) is presented. In the first study, data from 161 Asian American respondents were subjected to an exploratory factor analysis, which yielded 3 subscales composed of Socio-Historical Racism (14 items), General Racism (8 items), and Perpetual Foreigner Racism (7 items). The data also revealed initial evidence of AARRSI's reliability and concurrent and discriminant validity. In the second study, data from 142 Asian American respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
285
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 168 publications
(296 citation statements)
references
References 41 publications
8
285
3
Order By: Relevance
“…These studies were Chung, Kim, and Abreu (2004); Kim and Atkinson (2002); Kim et al (1999); ; Kim, Hill, et al (2003); Kim, Li, and Ng (2003); Kim and Omizo (2003);and Liang, Li, and Kim (2004).…”
Section: Methodsmentioning
confidence: 99%
“…These studies were Chung, Kim, and Abreu (2004); Kim and Atkinson (2002); Kim et al (1999); ; Kim, Hill, et al (2003); Kim, Li, and Ng (2003); Kim and Omizo (2003);and Liang, Li, and Kim (2004).…”
Section: Methodsmentioning
confidence: 99%
“…Until the 1990s, generally it was thought that the target of racial discrimination was African Americans even if others were targeted as well. However, there have been increased reports of anti-Asian incidents in the past two decades (Liang, Li, & Kim, 2004) as the Asian immigrant population has rapidly grown. Several studies have reported a strong relationship between perceived racial discrimination and mental health, even if no actual discrimination existed (Juang & Cookston, 2009;Noh & Kaspar, 2003;Yoo & Lee, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…According to Liang et al (2004) Asian Americans are able to excel and function well in a society, thereby masking the real discrimination and prejudice experienced by them (Delucchi & Do, 1995;Liang et al, 2004).…”
Section: Racismmentioning
confidence: 99%
“…Furthermore, there is a lack of published instruments designed to assess racism and experiences related to racism (Harrell, 1999;Liang et al, 2004).…”
Section: Cultural Systems Frameworkmentioning
confidence: 99%
See 1 more Smart Citation